Ce and Fe doped LaNiO3 synthesized by micro-emulsion route: Effect of doping on visible light absorption for photocatalytic application. (20th August 2021) - Ghafoor, Aamir; Bibi, Ismat; Majid, Farzana; Kamal, Shagufta; Ata, Sadia; Nazar, Nosheen; Iqbal, Munawar; Raza, Muhammad A S; Almoneef, Maha M
Abstract: A series of La1−x Cex Ni1−y Fey O3 (x, y = 0.00–0.25) NPs was fabricated via micro-emulsion route and effect of doping was investigated on the basis of optical, photocatalytic and structural properties. The as-synthesized NPs were characterized via XRD, Raman analysis, SEM and UV–visible techniques. The XRD results confirmed the rhombohedral perovskite phase particles with particles of 60–80 nm range. UV–vis absorption edge showed significant red shift thereby tuning the band gap from 2.77 to 2.64 eV. The photocatalytic effectiveness of LaNiO3 and La0.80 Ce0.20 Ni0.80 Fe0.20 O3 catalysts was performed by degrading Congo red (CR) dye under visible light exposure. Substituted catalyst exhibited superior photodegradation by showing 97% degradation in comparison to pristine LaNiO3 (63% only) in 120 min. Degradation of CR followed the pseudo fist order kinetics. In addition, the catalyst dose effect, dye concentration and pH variation was studied for Cr dye degradation. Enhanced photocatalytic activity and narrow bandgap of Ce and Fe doped LaNiO3 introduce such materials as efficient visible active photocatalysts to be utilized in dye removal application from waste water and in photovoltaic applications, respectively.